(untitled) (Journal of Partial Differential Equations, 1995)
A two-phase Stefan problem with the heat flux boundary conditions, including an unknown function f, is considered. The existence, uniqueness, and continuous dependence upon the initial data of the solution (f, s, u_1, u_2) are proved.